Development of Lactic Ester as Bifunctional Additive of Methanol-Gasoline - Zhang, Jie; Yang, Changchun; Tang, Ying; Xu, Lianghong; Wang, Xiaoting (Asian Journal of Chemistry, 2014)
In this paper, lactic esters were synthesized and used as phase stabilizer and saturation vapor pressure depressor of methanol-gasoline. The results show that the stabilities of the methanol-gasoline depend on the length of the lactic esters' alkoxy group. Several lactic esters were found to be effective in various gasoline-methanol blends, and the lactic esters display high capacity to depress the saturation vapor pressure of methanol-gasoline. According to the results, it can be concluded that the lactic esters have the great potential to be bifunctional gasoline-methanol additives.